New fluorescent auxin probes visualise tissue-specific and subcellular distributions of auxin in Arabidopsis - Pařízková, Barbora; Žukauskaitė, Asta; Vain, Thomas; Grones, Peter; Raggi, Sara; Kubeš, Martin F; Kieffer, Martin; Doyle, Siamsa M; Strnad, Miroslav; Kepinski, Stefan; Napier, Richard; Doležal, Karel; et al. (The New phytologist, 2021)
In a world that will rely increasingly on efficient plant growth for sufficient food, it is important to learn about natural mechanisms of phytohormone action. In this work, the introduction of a fluorophore to an auxin molecule represents a sensitive and non-invasive method to directly visualise auxin localisation with high spatiotemporal resolution. The state-of-the-art multidisciplinary approaches of genetic and chemical biology analysis together with live cell imaging, liquid chromatography-mass spectrometry (LC-MS) and surface plasmon resonance (SPR) methods were employed for the characterisation of auxin-related biological activity, distribution and stability of the presented compounds in Arabidopsis thaliana. Despite partial metabolisation in vivo, these fluorescent auxins display an uneven and dynamic distribution leading to the formation of fluorescence maxima in tissues known to concentrate natural auxin, such as the concave side of the apical hook. Importantly, their distribution is altered in response to different exogenous stimuli in both roots and shoots. Moreover, we characterised the subcellular localisation of the fluorescent auxin analogues as being present in the endoplasmic reticulum and endosomes. Our work provides powerful tools to visualise auxin distribution within different plant tissues at cellular or subcellular levels and in response to internal and environmental stimuli during plant development.
Keywords: regulace genové exprese u rostlin; proteiny huseníčku; kořeny rostlin; Plant Roots; regulátory růstu rostlin; in vivo visualisation; Arabidopsis Proteins; kyseliny indoloctové; transport; Plant Growth Regulators; Indoleacetic Acids; distribution; Gene Expression Regulation, Plant; subcellular localisation; Arabidopsis; fluorescent auxin